Alternative Fuels and Their Application to Combustion Engines - Rahman, S M Ashrafur (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The world is observing the disastrous consequences of climate change. The recent bushfires in Australia in 2019-2020 have burned 16.8 million hectares of land and killed 1 billion animals (estimated). Although diesel vehicles are widely used all over the world due their innate high power output, adaptability, and affordability; the transport sector is a significant contributor to carbon dioxide, which is immensely accountable for global warming. The production of cleaner alternatives to diesel fuel will help to build a sustainable environment for future generations. The Special Issue contains papers from experts around the world addressing the mentioned issues and suggesting pathways to improve.